(untitled) (Research, Society and Development, 2023)
Packaging serves its primary function to protect food and ensure its integrity and properties throughout the entire commercial process. In this context, the present article is a literature review that arises from the need to understand the application of food additives in polymeric films as sustainable alternatives to reduce waste generation and enhance food preservation and durability. A review of previous studies on the subject revealed that starch is the primary food additive used, and other additives are combined with it to enhance the advantages and characteristics of the films. The advancement of polymeric film studies is expected to bring significant benefits to the global population in terms of promoting conscious consumption, reducing waste, and minimizing the generation of solid waste disposed of in nature.